Analisis Yuridis Tindak Pidana Pencabulan Anak Di Bawah Umur - Warjiyati, Sri (Al-Jinayah: Jurnal Hukum Pidana Islam, 2018)
Abstract: Cases of crime on child often occur and the number of the crime is increasing every year. Molestation is a violation of the child's rights and cannot be justified regardless of the reason, both in moral and religious term. Child has right to be protected for his or her welfare, because child is vulnerable group of community. In positive law, Article 82 of Law Number 23 of 2002 concerning Child Protection, explains that the perpetrators of the crime on child are subject to a maximum sentence of 15 years and a minimum of 3 years in prison with a maximum fine of 300,000,000.00 and at least 60,000,000. 00. Whereas in Islamic criminal law, sexual abuse is equated with adultery and the perpetrators of which are stoned to death, while those of the ghair muhshan are flogged a hundred times and exiled.Keywords: Positive law, Islamic criminal law, child abuse, KPAI.   Abstrak: Kasus kejahatan pada anak seringkali terjadi dan jumlah kejahatannya setiap tahun semakin bertambah. Pencabulan merupakan pelanggaran hak anak dan tidak dapat dibenarkan bagaimanapun alasannya, baik dari segi moral, susila dan agama. Anak memiliki hak untuk dilindungi demi kesejahteraannya, karena anak-anak merupakan golongan yang rawan. Pada hukum positif, Pasal 82 Undang-Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak, dijelaskan bahwa para pelaku kejahatan pada anak dikenai hukuman maksimal 15 tahun dan minimal 3 tahun penjara dengan denda paling banyak 300.000.000,00 dan paling sedikit 60.000.000,00. Sedangkan dalam hukum pidana Islam, pencabulan disamakan dengan zina dan para pelaku yang muhshan dirajam hingga mati, adapun yang ghair muhshan dicambuk seratus kali dan diasingkan. Kata Kunci : Hukum Positif, Hukum Pidana Islam, Pencabulan Anak, KPAI.